Human governance and employee compensation: A conceptual framework - Hanapiyah Z.M.; Daud S.; Wan Abdullah W.M.T.; Zainol Z. (American Scientific Publishers, 2023)
Human governance is crucial in determining behavior and performance of employees. The employees are important in leading the organizations success with a certain level of commitment and effort. Apart from that, compensation is one of the most complex and dynamic issues that reflect the performance of employees in the organization. The aim of this paper is to propose a conceptual framework to examine the effect of human governance on employee compensation. The proposed framework is based on the theoretical framework that includes two main variables consist of human governance and employee compensation. It is expected that there is a significant relationship between human governance and employee compensation and findings from an empirical study will improve the existing formulation of employee compensation that will maximize employees satisfaction. 2017 American Scientific Publishers. All rights reserved.